PENGARUH PENERAPAN MODEL PEMBELAJARA PROJECT BASED LEARNING (PJBL) TERHADAP PERKEMBANGAN KREATIVITAS PESERTA DIDIK KELAS III MATA PELAJARAN IPAS MI AL-HUDA PLOSO - Irma Masitoh; Nelli Fauziah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Science and Social Studies (IPAS) learning in the third grade at MI Al-Huda Ploso was still dominated by teacher-centered learning, causing students to be passive and limiting the development of their creativity. Therefore, a more innovative and student-centered learning model was needed. One appropriate model is Project Based Learning (PjBL), which provides meaningful learning experiences through project-based activities to enhance students' creativity. This study aimed to determine the implementation of the Project Based Learning (PjBL) model and to analyze its effect on the development of students' creativity in the IPAS subject for third-grade students at MI Al-Huda Ploso. This research employed a quantitative approach using a Quasi-Experimental Design with a Nonequivalent Control Group Design. The participants consisted of an experimental class and a control class, each comprising 29 students. Data were collected through observation, tests, and documentation, and analyzed using descriptive statistics, normality tests, homogeneity tests, and the Independent Samples t-test. The results showed that the implementation of the Project Based Learning (PjBL) model was carried out effectively and created an active, collaborative, and student-centered learning environment. The average score of the experimental class increased from 65.52 in the pre-test to 74.00 in the post-test, while the control class increased from 65.00 to 72.00. The hypothesis test showed a significance value of Sig. (2-tailed) < 0.001, indicating that H₀ was rejected and H₁ was accepted. Therefore, the Project Based Learning (PjBL) model had a significant positive effect on the development of students' creativity in the IPAS subject for third-grade students at MI Al-Huda Ploso.